2003
DOI: 10.1097/01.tp.0000054230.63568.79
|View full text |Cite
|
Sign up to set email alerts
|

Experience of liver transplantation for incurable alveolar echinococcosis: a 45-case European collaborative report

Abstract: This unique experience indicates that LT is feasible for life-threatening AE. Specific management is needed to optimize the results: earlier decision for LT in incurable symptomatic biliary AE, pre- and post-LT BZM therapy, meticulous pre-LT evaluation to identify extrahepatic extension, and an immunosuppressive regimen kept to a minimum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(107 citation statements)
references
References 17 publications
2
92
0
9
Order By: Relevance
“…Liver transplantation has provided a life‐saving technique for patients with “unresectable” but not metastatic HAE lesions 11, 13, 14, 31, 32, 33, 34, 35. Several centers had reported their work, which was summarized in Table 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver transplantation has provided a life‐saving technique for patients with “unresectable” but not metastatic HAE lesions 11, 13, 14, 31, 32, 33, 34, 35. Several centers had reported their work, which was summarized in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…The most important advantage of an autologous graft over an artificial one is better biocompatibility, which greatly reduces the risk of graft rejection while reducing the postoperative anticoagulant therapy, thus reducing the possibility of postoperative bleeding 40, 41. In addition, the GSVs are easy to harvest, and their removal does not cause many adverse effects; all the preceding reasons make the GSV the ideal material for vascular reconstruction 26, 32, 35…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a number of studies that documented the outcomes for patients receiving a liver transplant because of advanced alveolar echinococcosis (45)(46)(47)211). A multicenter study performed in Europe showed an overall survival rate of 71% at 5 years, and in 58% of patients, there were no documented recurrences (211).…”
Section: Infections Caused By Echinococcus Sppmentioning
confidence: 99%
“…A multicenter study performed in Europe showed an overall survival rate of 71% at 5 years, and in 58% of patients, there were no documented recurrences (211).…”
Section: Infections Caused By Echinococcus Sppmentioning
confidence: 99%
“…Même si une ré-intervention a été COMMUNICATIONS nécessaire dans d'assez nombreux cas, surtout pour saignement, la transplantation est ainsi apparue comme une possibilité ultime de sauver ces malades. Des études ulté-rieures ont cependant montré (BRESSON-HADNI et al, 1999, KOCH et al 2003 que des métastases extra-hépa-tiques, initialement infra-cliniques, se développent trop souvent, grevant le pronostic à long terme. Ceci est sans doute à rapprocher des résultats expérimentaux obtenus par LIANCE et al (1992), qui ont établi que la ciclosporine (qui doit être poursuivie en permanence après la transplantation) déprime les réponses immunitaires spécifiques contre le parasite et favorise la croissance larvaire.…”
Section: Traitementunclassified